Brokerage Firms under Information Asymmetry and its Effect on Common Stock Trade : Applied Research in the Iraq Stock Exchange - محمد, اياد طاهر; احمد, ميادة محمود (Journal of Economics and Administrative Sciences, 2018)
The research aims to Applied Study in the nature of the impact of information asymmetry for brokerage firms in the common stock trading, The research included the theoretical concepts associated with each of the brokerage firms ,information asymmetry and common stock trading, It used the financial methods on the practical side of the information asymmetry for brokerage firms based in the sector as well as trading volume and spread for common stock , The community of the research included the Iraq Stock Exchange,the sample of research the companies listed which have been trading on its stock for the period August 2015 until December 2015 as well as brokerage firms amounting to 47 brokerage firm. The research based on amajor hypothesis that: " There is a statistically significant effect information asymmetry for brokerage firms on stock trading volume traded in which companies" and with  using the (SPSS 23) the hypothesis was testing by simple linear regression analysis, the research found  the most important conclusions: The information asymmetry for brokerage firms does not contributed in increasing the volume for common stock for companies it  traded , This indicates that high trading volume are not depends the existence of information asymmetry for brokerage firms in the Iraq Stock Exchange .Either important recommendations: Oblige the brokerage firms on the Iraq Stock Exchange to provide information about the common stock traded through financial analysts, and it is recommended in case study information asymmetry for brokerage firms stand on of the information asymmetry measures represented by  spread and trading volume and volatility on the prices of common stock associated positively with common stock prices under information asymmetry.